Pengaruh Akupresur terhadap Dismenorea pada Mahasiswi Program Studi DIII Kebidanan STIKes Baiturrahim - Julaecha Julaecha; Tina Yuli Fatmawati; Ajeng Galuh Wuryandari (Universitas Baiturrahim, 2023)
Menstrual pain is a natural thing experienced by women during menstruation. The prevalence of dysmenorrhea in Indonesia is 54.98% for primary dysmenorrhea and 9.36% for secondary dysmenorrhea. One way to deal with dysmenorrhea with acupressure therapy is traditional non-pharmacological therapy, namely by massaging acupuncture points/certain body points to improve blood circulation, the body secretes endorphins causing the body to relax, not worry so that menstrual pain decreases/disappears. This study aims to determine the effect of acupressure on reducing dysmenorrhea. The method used in this study was a quasi-experimental one group pre post test design. The population in this study were all female students of the D III Midwifery STIKes Baiturrahim study program. The sample in this study used a total sampling of 42 female students who experienced primary dysmenorrhea. The research process went through several stages, the first was measuring pain scale during menstruation, the second stage was giving acupressure intervention at Hequ (LI4), Sayinjiao, (SP6) and Zusanli (ST 36) points. Acupressure is done 3 days before and the first 3 days during menstruation, done 2 times a day or when pain occurs, the third stage is measuring pain scale during menstruation after the intervention. The instrument used to measure the pain scale is the Numeric Rating Scale (NRS). The collected data were analyzed by univariate and bivariate. The results of the research analysis showed that before the intervention was given the average pain intensity was 2.67 and the SD was 0.678 and after the intervention was given the average pain intensity was 2.45 and the SD was 0.705, the decrease in pain intensity was 0.22 with a p value of 0.000. It can be concluded that acupressure has an effect on reducing pain during menstruation . The results of this study are expected as information for young women during menstruation